VIRGINITY DALAM MAJALAH GADIS: Periode Tahun 2006-2012 - DEWA AYU PUTU MARIANA KENCANAWATI; ZAHROH SHALUHIYAH (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Sex And Virginity Myth In GADIS Magazine (2006-2012)Background, The taboo to talk about sexuality in the public pace makes myth about sex developed more rapidly in teenager. Mostly that myth is false, so their attitute in sexuality become wrong either.One of all media that giver teenageinformation about sexuality is magazine. GADIS magazine is the first gril magazine in Indonesia. Since 2006, GADIS magazine gives information about sexualit in sexita rubric. That’s why very important to know about myth of sexuality in GADIS magazine since 2006-2012. The aim of this research is have a depoiction about myth of sexuality ion GADIS magazine. Method, This research use Interactionism simbolic approach, with tematic content analysis anda the eksplanation was complete with kualitatif method, the saple of this research use purposive sampling with 72 magazine. Result, GADIS depict two myth of sexuatity they are about sexual behaviour (all thing are link with pregnancy) and virginity (All about virgin sign). GADIS gives a short right explanation about this myth but reader can not interpreat it right. So I Suggest, to make a forum discussion about teen virginity issue and publish the result in media.